Cultivating Civic Virtue and Educating for Peace: Insights from Transitional Justice - Snyder, Joshua R. (Journal of the Society of Christian Ethics, 2025)
Transitional justice seeks to address how democratic transitions take place following a period of repressive rule or internal conflict. Peace education is essential as a divided society moves from violence toward the peaceful, pluralistic coexistence of former adversaries. By focusing on the Guatemalan Catholic Church, this essay demonstrates the value of a localized, religious approach for transitional justice. It shows how religion can play a positive, public role in facilitating transitional justice initiatives and how the Guatemalan Catholic Church did this through its pastoral approach to peace education.